2012
DOI: 10.1128/jcm.01143-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus Isolates from Patients Newly Identified as Nasal Carriers

Abstract: We aimed to determine whether additional molecular and microbiological evaluations of methicillin-resistant Staphylococcus aureus (MRSA) isolated from patients newly identified as nasal carriers were useful for control strategies and whether longitudinal testing during the same or repeat hospitalization changed MRSA status. Nasal swabs from patients positive by Xpert MRSA PCR and not known to be colonized in the previous year were cultured for S. aureus. Isolates were tested for resistance to a variety of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Several studies demonstrated that patients are frequently recolonized after treatment (9,21), and they also associated the use of mupirocin with increased rates of resistance (7). In our facility, the baseline level of mupirocin resistance in isolates from patients who had received mupirocin therapy was low (9%), which was comparable to reports from other VA hospitals (19). Of the patients in our study who were recolonized after mupirocin therapy, 30% were recolonized with a different strain.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several studies demonstrated that patients are frequently recolonized after treatment (9,21), and they also associated the use of mupirocin with increased rates of resistance (7). In our facility, the baseline level of mupirocin resistance in isolates from patients who had received mupirocin therapy was low (9%), which was comparable to reports from other VA hospitals (19). Of the patients in our study who were recolonized after mupirocin therapy, 30% were recolonized with a different strain.…”
Section: Discussionsupporting
confidence: 80%
“…Isolates from the outpatient group, nares conversion isolates, and isolates classified as strain types USA100 and USA300 demonstrated significant differences from the overall rates. Although USA300 remains a predominant strain type in the United States, the distribution of strain types varies among VA hospitals (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have a positive carriage pattern on the initial hospitalization continue to carry MRSA either always or intermittently over long periods of time [13]. The benefit of repeated MRSA screening in these patients is unclear, since most will not have the consistently negative result over 3 consecutive tests in the absence of antibiotic exposure that would be required to move the patient out of the “MRSA-colonized” category.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not account for MSSA colonization or differences in virulence among nasal MRSA isolates that could have impacted infection risk. Our recent molecular evaluation of nasal MRSA and MSSA among newly colonized veterans identified a low prevalence of USA300 and Panton-Valentine Leukocidin (PVL) genes and no association between USA300 MRSA carriage and subsequent infection risk [13].…”
Section: Discussionmentioning
confidence: 99%
“…These includes Acinetobacter baumannii ATCC19606, Escherichia coli ATCC29522, Staphylococcus aureus ATCC29523, Staphylococcus epidermidis ATCC12228 (as representatives of Gram-positive and Gram-negative bacteria), and two antibiotic-resistant strains of methicillin-resistant S . aureus (MRSA) BBA1680, USA300 and BBA1683, USA400 [ 31 , 32 ]. E .…”
Section: Methodsmentioning
confidence: 99%